Gadamer's Hermeneutic Analysis For Digital Illustration Barong & Rangda On Emba Jeans By Illustrator Monez - Ni Nyoman Sri Witari; I Wayan Swandi; I Wayan Setem; Alit Kumala Dewi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Emba Jeans products promoted in the July 2023 season are rich in Balinese tradition, transforming the figures of Barong and Rangda as objects of creativity. The reproduction of the meaning of the text contained in the illustrations is very unique and rich with interpretations This study aims to describe relevant interpretations and understandings to explore the meaning and aesthetic value of Monez's digital illustrations that compose Barong and Rangda as the main characters on Emba Jeans products with the theme